Exercise and Depression: The Role of Physical Activity in Mental Health - Majewska, Melania; Piasecka, Natalia; Rafalska, Izabela; Smagoń , Jakub; Kornacka, Natalia; Kaim, Martyna; Bober, Joanna; Bochenek, Magdalena; Siewiera, Wiktoria; Bednarski, Krzysztof; et al. (Quality in Sport, 2026)
Depressive disorders represent a major global health burden and are associated with significant impairment in quality of life and increased risk of comorbid conditions. Despite the availability of conventional treatments, a substantial proportion of patients do not achieve full remission, highlighting the need for complementary therapeutic strategies. In recent years, physical activity has emerged as a promising and accessible intervention for both the prevention and treatment of depression. This narrative review aims to summarize current evidence on the role of physical activity in mental health, with particular emphasis on the underlying biological and psychological mechanisms. Exercise has been shown to influence multiple pathways implicated in the pathophysiology of depression, including modulation of inflammatory processes, regulation of the hypothalamic–pituitary–adrenal axis, enhancement of neuroplasticity, and effects on neurotransmitter systems. In addition, psychological mechanisms such as improved self-perception, stress reduction, behavioral activation, and increased social interaction contribute to the antidepressant effects of physical activity. Evidence from observational studies and meta-analyses indicates that regular physical activity is associated with a reduced risk of developing depression and may significantly alleviate depressive symptoms in affected individuals. Furthermore, physical activity represents a low-cost, widely accessible intervention with minimal side effects, making it a valuable component of both clinical practice and public health strategies. In conclusion, physical activity plays a multidimensional role in the prevention and management of depression and should be considered an integral part of comprehensive mental health care. These findings highlight the importance of incorporating physical activity into comprehensive treatment strategies for depression.